2013
DOI: 10.1177/2048872613508658
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ST-segment resolution and anterior infarct size after primary percutaneous coronary intervention: analysis from the INFUSE-AMI trial

Abstract: Aims: ST-segment resolution (STR) after reperfusion therapy has been shown to correlate with prognosis in patients with ST-segment elevation myocardial infarction (STEMI). We investigated whether acute ECG measurements also correlate with ultimate infarct size. Methods and Results:The INFUSE-AMI trial randomized 452 patients with anterior STEMI to intracoronary bolus abciximab vs. no abciximab, and to thrombus aspiration vs. no aspiration. Infarct size as percentage of total LV mass was calculated by cardiac m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Previous studies showed that poor STR is a good predictor of poor microvascular flow recovery and inferior clinical outcomes. 15 , 16 This was also confirmed by our findings that patients with CMR-MVO had worsened STR than those without MVO. In the meanwhile, we found that STE (ie, maximal STE and sum STE) was also correlated with MVO.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies showed that poor STR is a good predictor of poor microvascular flow recovery and inferior clinical outcomes. 15 , 16 This was also confirmed by our findings that patients with CMR-MVO had worsened STR than those without MVO. In the meanwhile, we found that STE (ie, maximal STE and sum STE) was also correlated with MVO.…”
Section: Discussionsupporting
confidence: 81%
“…ST-segment changes are better indicators for myocardial rather than epicardial flow, thus help to enhance prognostic value of coronary angiography alone. 15 18 Several studies have suggested that a simple serial electrocardiogram (ECG) analysis could be very helpful to identify MVO in patients with STEMI treated with PCI. 19 22 However, the relationship between different parameters of ST-segment change and IMH still remains to be clarified and which parameter is the most practicable predictor for detecting cardiac magnetic resonance(CMR)-derived MVO or IMH is conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by the association of EAT with MVO and ST-deviation. Both parameters mirroring disturbed microcirculation [ 32 ], correlate with infarct size [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of cases without ST-segment elevation develop unstable angina pectoris or AMI without a Q wave, with a few developing AMI with a Q wave. ST-segment elevation changes into ST-segment depression when an oxygen-free environment persists 8…”
Section: Introductionmentioning
confidence: 99%